Considerations to Improve Pediatric HIV Testing and Close the Treatment Gap in 16 African Countries. Issue 2 (23rd November 2022) - Gross, Jessica; Medley, Amy; Rivadeneira, Emilia; Battey, Katherine; Srivastava, Meena; Grillo, Michael; Wolf, Hilary; Simmons, Paige; Hast, Marisa; Patel, Monita
Abstract : Background: In 2019, South Africa, Nigeria, Tanzania, Democratic Republic of Congo, Uganda, Mozambique, Zambia, Angola, Cameroon, Zimbabwe, Ghana, Ethiopia, Malawi, Kenya, South Sudan and Côte d'Ivoire accounted for 80% of children living with HIV (CLHIV) not receiving HIV treatment. This manuscript describes pediatric HIV testing to inform case-finding strategies. Methods: We analyzed US President's Emergency Plan for AIDS Relief monitoring, evaluation, and reporting data (October 1, 2018 to September 30, 2019) for these 16 countries. Number of HIV tests and positive results were reported by age band, country, treatment coverage and testing modality. The number needed to test (NNT) to identify 1 new CLHIV 1–14 years was measured by testing modality and country. The pediatric testing gap was estimated by multiplying the estimated number of CLHIV unaware of their status by NNT per country. Results: Among children, 6, 961, 225 HIV tests were conducted, and 101, 762 CLHIV were identified (NNT 68), meeting 17.6% of the pediatric testing need. Index testing accounted for 13.0% of HIV tests (29.7% of positive results, NNT 30), provider-initiated testing and counseling 65.9% of tests (43.6% of positives, NNT 103), and universal testing at sick entry points 5.3% of tests (6.5% of positives, NNT 58). Conclusions: As countries near HIV epidemic control for adults, the need to increase pediatric testing continues. Each testing modality – PITC, universal testing at sick entry points, and index testing – offers unique benefits. These results illustrate the comparative advantages of including a strategic mix of testing modalities in national programs to increase pediatric HIV case finding.